FOLKLORE-BASED SERIAL IMAGE MEDIA IN LEARNING TO WRITE NARRATIVE TEXT - Cahyono, Bambang Eko Hari; Putri Pratiwi, Cerianing; Mulyaningsih, Indrya (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to describe the development of folklore-based serial image media in learning to write narrative texts for elementary school students. This research uses a development research approach using ADDIE (analysis, design, development, implementation, evaluation). Exploratory studies were conducted in 10 elementary schools and trials were conducted in 3 elementary schools in the Madiun City area. Data collection in exploratory studies used observation, interviews, and documents, while questionnaires were used to obtain input and assessment from experts, teachers, and students. Data analysis techniques use descriptive analysis. The results showed that folklore-based serial image media is feasible to be used in learning to write narrative texts for elementary school students. Folklore-based serial image media has also proven effective in improving students' narrative text skills.